PENINGKATAN KEMAMPUAN MENULIS LAPORAN HASIL OBSERVASI DENGAN MENGGUNAKAN MEDIA CHROMEBOOK DI KELAS VIII SMP NEGERI 2 LEMBAK KABUPATEN MUARA ENIM - Pratiwi, Hayyu; Yessi Fitriani; Puspa Indah Utami (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
This study aims to improve the writing skills of Observation Reports (LHO) of eighth-grade students of SMP Negeri 2 Lembak, Muara Enim Regency through the use of Chromebook media in Indonesian language learning. The study used a Classroom Action Research (CAR) design with two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 23 eighth-grade students. Data collection was carried out through writing tests, student participation observation sheets, and motivation questionnaires. Learning strategies included project-based learning, the use of Google Classroom, and Chromebook-assisted group discussions. The results showed a significant increase in students' LHO writing skills. The average score increased from 61.4 (pre-cycle) to 70.0 (cycle I) and 81.6 (cycle II). Learning completeness increased from 26% to 95.65%. Student active participation also increased from 26% to 95.65%, reflecting a significant increase in learning motivation. Chromebooks have proven effective through their ease of real-time revision, collaboration between students, and rapid feedback. This study was limited to a single school with a limited number of subjects, so generalization of the findings should be done with caution.  These findings provide practical implications for Indonesian language teachers integrating Chromebook technology into writing instruction. Socially, the use of digital media promotes students' technological literacy in developing regions. This study provides a original contribution by demonstrating the effectiveness of Chromebooks as a learning medium for LHO writing in junior high schools in rural Indonesia. Keywords: Chromebooks; Writing; Observation Results Sheet; Classroom Action Research.